Analysis of Criteria for Supplier Selection of Soybean Raw Materials Using the Analytical Hierarchy Process (AHP) Method at Sagala Tofu and Tempeh MSMEs - Manurung, Liony Apriyanti; Harlan, Fandy Bestario (Journal of Applied Business Administration, 2025)
Sagala Tofu and Tempeh MSMEs face challenges in selecting soybean suppliers due to inconsistencies in price, quality, and delivery reliability, which impact production and market demand fulfillment. Sagala Tofu and Tempe MSME is one of the MSMEs that requires 100–150 kg of soybeans daily. This research aims to help Sagala Tofu and Tempe MSME identify the correct standards (priority criteria/sub-criteria) for making decisions regarding soybean raw materials and to determine the best soybean supplier. The research method used is the Analytical Hierarchy Process (AHP). The results show that the priority criterion is quality (0.469), followed by price (0.230), quantity accuracy (0.159), delivery (0.102), and customer care (0.038). Based on these supplier selection criteria, supplier X was rated the best, with a score of 0.420, followed by supplier Z (0.340) and supplier Y (0.240).